SPECIFICS OF THE REALITIES TRANSLATION MODEL (Analysis of International Sciences, 2024)
The model of translating realities encompasses specific features that are essential for accurately capturing and conveying the essence of different realities. This article explores these features, highlighting their importance in achieving effective translation of various aspects of reality. The discussed features include context sensitivity, cultural adaptation, semantic precision, stylistic nuance, and ethical considerations. Understanding and incorporating these features into the translation process can significantly enhance the quality and fidelity of translated realities.